Adaptive model of project management in the field of innovative engineering developments: integrating waterfall and agile for dynamic requirements - Myronenko, Oleksii (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is project management in the field of innovative engineering developments and management of scientific projects under conditions of dynamic requirements, high complexity, and variable implementation deadlines. The study addressed the issue of insufficient flexibility of the Waterfall methodology for adapting to changing conditions and the lack of clear deadlines in the Agile methodology, which is critically important for engineering and scientific projects. In the process of the study, the problems of conventional methodologies were analyzed, an expanded list of project input parameters were formed, and an analysis algorithm was developed that makes it possible to determine the feasibility of using Waterfall and Agile elements at each stage of project implementation. Using the advantages of the Waterfall and Agile methodologies and eliminating their shortcomings is possible within the framework of an adaptive model of scientific and innovative project management. The results of the study show that the model devised provides effective resource management, reducing implementation deadlines and increasing stakeholder satisfaction. The integration of the Waterfall structure and Agile iterativeness makes it possible to avoid the shortcomings of each of the methodologies, ensuring greater adaptability and accuracy in achieving goals. The proposed model helps optimize project management under conditions of high uncertainty and changing market conditions. The results could be used by companies to improve the management of engineering and scientific projects, especially in industries where rapid adaptation to changes and ensuring predictability of results are important. This study also contributes to the formation of a new approach to project management, which takes into account the specificity of modern innovative developments